Dependent Personality in a Case of Sexual Offence on a Child (A Case Study) - Hudi Winarso; Roni Subagyo (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
This discussion is aimed on analyzing the fatal sexual violence incident that occurred in Kediri, East Java on June 27th, 2016. The victim was a three year old boy who was sodomized and thrown to his death by the perpetrator. The perpetrator himself is the victim’s uncle (30 years of age), who experienced relatively heavy stress, and an MMPI (Minnesota Multi-phasic Personality Inventory) indicating normal (heterosexual) sexual orientation, a modest and honest man with a dependent personality. Data was obtained from patient’s medical records, interview with psychiatrist in charge of the event, and the mother of the perpetrator to detect influential factors starting from conception to adulthood. An important data is that the perpetrator was once a victim of sexual violence (sodomy) when he was in the first year of primary school, the stressful burden in the family’s environment, personal trauma of wife’s miscarriage when the embryo was four months old that occurred one month prior to the incident.